Determination of Firing Distance by Gunpowder Residue Concentration Analysis - Carrera Palao, Rosa (1999)
OBJECTIVE: To assess an appropriate diagnostic method by measurements of the gunpowder amount around the entrance hole on the skin. METHODOLOGY: Using a caliber-38 revolver with FAME bullets, and from pre-established distances, five series of gunshots were performed on clothed fragments of pigskin. Then, we verified the presence of gunpowder tattoos, both, over the skin and clothes. To determine the amount of gunpowder particles present on the skin, microphotografies of the specimens were taken. All firing distances drew a clean zone (peripheral to the bullet entrance hole); followed by the gunpowder tattoo, which were divided into three concentric areas. These areas are closely related to the firing distance and inversely related to the concentration of gunpowder particles. CONCLUSION: It´s possible to make an accurate asessment of firing distance (range: 30 to 100 cm), through the measurement of gunpowder residues around the entrance hole on the skin, as showed in microphotographies. We propose the term "target-like tattoo" for these skin images.